Analyzing the Quenchable Iron Pool in Murine Macrophages by Flow Cytometry - Michael Riedelberger; Karl Kuchler (Bio-Protocol, 2020)
Tissue-resident macrophages are pivotal for a tightly-regulated iron metabolism at a cellular and systemic level, since subtle iron alterations increase the susceptibility for microbial infections or drive multiple diseases. However, research on cellular iron homeostasis in macrophages remains challenging due to the limited amount of available methods using radioactive 59Fe isotopes or strong iron chelators, which might be inapplicable in certain experimental settings. This protocol describes the analysis of the quenchable iron pool (QIP) in macrophages by loading these cells with exogenous iron-complexes. Thereby, the cytoplasmic iron pool can be determined, since the iron uptake ability of macrophages inversely correlates with intracellular iron levels. Thus, this assay enables the accurate analysis of even minor alterations in cytoplasmic iron fluxes and is applicable in almost every laboratory environment. In addition, the protocol can also be adopted for other immune cell types in vitro and in vivo.